2023
DOI: 10.1108/ebhrm-10-2022-0252
|View full text |Cite
|
Sign up to set email alerts
|

Workplace pressure, employee stress, mental well-being and resilience in response to COVID-19 in Singapore

Graeme Ditchburn,
Rachel Evangeline Koh

Abstract: PurposeCOVID-19 forced organizations to implement protective measures changing how employees worked; however, empirical evidence is needed to explore how employees responded. This study examines the impact of COVID-19-related organizational changes in Singapore on employees’ perceptions of work pressure, stress and mental well-being (MWB) and the mediating role of resilience.Design/methodology/approachThis study used a cross-sectional, anonymous online survey of 157 full-time employees who had worked for at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The fifth hypothesis investigated a model which proposes that the relationship between psychological and work well-being is mediated by resilience. Ditchburn and Koh (2023) found that resilience can mitigate the negative impact of distress on work well-being by helping school leaders develop coping strategies. Resilience serves as a protective shield against escalating work pressure while concurrently fostering the preservation of psychological well-being (Chen and Chi-Kin Lee, 2022; Ditchburn and Koh, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fifth hypothesis investigated a model which proposes that the relationship between psychological and work well-being is mediated by resilience. Ditchburn and Koh (2023) found that resilience can mitigate the negative impact of distress on work well-being by helping school leaders develop coping strategies. Resilience serves as a protective shield against escalating work pressure while concurrently fostering the preservation of psychological well-being (Chen and Chi-Kin Lee, 2022; Ditchburn and Koh, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Ditchburn and Koh (2023) found that resilience can mitigate the negative impact of distress on work well-being by helping school leaders develop coping strategies. Resilience serves as a protective shield against escalating work pressure while concurrently fostering the preservation of psychological well-being (Chen and Chi-Kin Lee, 2022; Ditchburn and Koh, 2023). Furthermore, studies have shown (e.g.…”
Section: Introductionmentioning
confidence: 99%